1991
DOI: 10.1002/mds.870060208
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of parkinsonism by antagonism of excitatory amino acid transmission in the medial segment of the globus pallidus in rat and primate

Abstract: Recent experimental data has made possible the description of the pathophysiological circuitry that mediates parkinsonism. This work has shown that dopamine-denervated striatal cells discharge abnormally and that this ultimately causes cells in the medial segment of the globus pallidus to become abnormally overactive. The main driving force behind the overactive cells in the medial pallidal segment appears to be excess activity in the afferent pathway to it from the subthalamic nucleus. This pathway is known t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
84
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(91 citation statements)
references
References 10 publications
7
84
0
Order By: Relevance
“…Recent studies have provided better understanding of the functional organization of the basal ganglia circuitry and the pathophysiological mechanisms of PD. [1,3,4,6,7] In summary, the loss of dopaminergic nigrostriatal neurons is thought to result in a dysfunction of the two parallel segregated striatopallidal pathways. In the indirect pathway, increased activity of the inhibitory striato-GPe projection reduces the firing of inhibitory GPe neurons projecting to the subthalamic nucleus (STN).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have provided better understanding of the functional organization of the basal ganglia circuitry and the pathophysiological mechanisms of PD. [1,3,4,6,7] In summary, the loss of dopaminergic nigrostriatal neurons is thought to result in a dysfunction of the two parallel segregated striatopallidal pathways. In the indirect pathway, increased activity of the inhibitory striato-GPe projection reduces the firing of inhibitory GPe neurons projecting to the subthalamic nucleus (STN).…”
Section: Discussionmentioning
confidence: 99%
“…Local administration of non-NMDA antagonists into basal ganglia output nuclei produced marked anti-akinetic effects in animals with parkinsonian symptoms (Brotchie et al 1991(Brotchie et al , 1992Graham et al 1990;Klockgether et al 1991). It was suggested that these effects are brought about by a blockade of non-NMDA receptors in basal ganglia output nuclei which are overactive in this condition.…”
Section: Discussionmentioning
confidence: 99%
“…These results are particularly important because the non-competitive NMDA-antagonist MK-801, although effective in rodent models of Parkinson's disease, was not active in the MPTP-treated common marmoset when administered alone (Close et al, 1990) and did not exert additive effects to L-Dopa in another primate species (Crossman et al, 1989) in the same model. In contrast, CPP (Crossman, personal communication) and the glutamate antagonist kynurenate reverse akinesia in the MPTP-treated common marmoset following focal injection into the medial pallidum (Brotchie et al, 1991). Lesion of the subthalamic nucleus by focal injection of the neurotoxin ibotenic acid also ameliorates parkinsonian symptomatology in MPTP-treated green monkeys (Bergman et al, 1990).…”
Section: Discussionmentioning
confidence: 99%